Gagasan Komunikasi Islam dalam Karya Sarjana Komunikasi di Indonesia - Holy Rafika Dhona; Risky Wahyudi (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2022)
This article aims to examine how academics in the field of communication comprehend Islamic communication as represented within scientific publications, especially scientific journals. This study reports on how academics discuss Islamic communication within 227 articles published in Indonesian journals indexed by Garba Reference Digital (Garuda) for the 2016-2020 period. Using descriptive quantitative content analysis, this study states that most Islamic communication writings tend to position Islam as